Comparative study on in-plane compression properties of 3D printed continuous carbon fiber reinforced composite honeycomb and aluminum alloy honeycomb. (July 2022) - Dou, Hao; Ye, Wenguang; Zhang, Dinghua; Cheng, Yunyong; Wu, Chenhao
Abstract: Additive manufacturing is a rising continuous fiber reinforced composite molding method, which has been developed and applied in many technical fields in the current research. In this investigation, a lightweight CCFR (Continuous Carbon Fiber Reinforced) composite honeycomb is proposed based on the continuous fiber additive manufacturing, and its performance under in-plane compression is presented. Through the analysis of experimental results of honeycombs with different materials, it is demonstrated that carbon fiber can not only enhance the mechanical properties, but also change the deformation characteristics of the structures. Under the loading direction X 2 (transverse direction), CCFR honeycomb, aluminum alloy honeycomb and unreinforced honeycomb (under the X 1 (longitudinal direction)/ X 2 load) all have multiple local failure, while the stress–strain curve presents several large fluctuations. When subjected to X 1 pressure, CCFR honeycombs have a relatively stable stress–strain curve, and the mechanical performance is more consistent with the elastic–plastic honeycomb formed by aluminum alloy material. As well as CCFR honeycomb exhibits the largest specific energy absorption when subjected to X 1 load, which is 186.58% and 596.84% higher respectively than that of pure PLA and aluminum alloy. Cone Beam Computed Tomography (CBCT) and Field Emission Scanning Electron Microscope (FESEM) are adopted to detect the test pieces, it is also found that CCFR honeycombs have no obvious local damage and brittle fracture under the pressure of X 1 . Highlights: 3D printed CCFR composite honeycomb has excellent mechanical properties and unique deformation characteristic. Trend of stress-strain curve loading in X 1 of 3D printed CCFR honeycomb is similar to the elastic-plastic honeycomb. 3D printed CCFR honeycomb exhibits the largest specific energy absorption loading in X 1 . Increase of strength and change of deformation characteristic, are all caused by the existence of continuous carbon fiber. Failure of the structure is mainly caused by the poor impregnation between the fiber and matrix.